Evaluation of the quality of family planning services from the perspective of service users using the SERVQUAL model in Sanandaj comprehensive health centers in 2018 - Rahil Gholipour (Patient Safety and Quality Improvement Journal, 2019)
Introduction: Family planning is aimed at improving the health and well-being of women, children and the family and affecting the quality of life and sexual health. Today, the quality of services has a profound effect on the economic situation. Knowing the expectations of service providers and checking the status of existing weaknesses and strength is revealed. The purpose of this study was to determine the quality of family planning services from the viewpoint of service recipients using the SERVQUAL model in Sanandaj comprehensive health centers in 2018. Methods: In this descriptive-analytical study, 384 women who received family planning services in Sanandaj comprehensive health centers were evaluated. Sampling was done by stratified random sampling. The data was collected by a SERVQUAL Questionnaire 22 pair questions with five dimensions. Data were analyzed by SPSS-23 software and descriptive statistics, t-test and ANOVA. P Results: The results of the study showed a negative gap in all aspects of quality. The highest gap was in the dimension of empathy (-1.84) and the lowest gap in the responsiveness dimension (-1.61). There was also no significant relationship between quality gap and demographic characteristics. Conclusion: The existence of a gap in the five dimensions of service quality suggests that at all levels, average expectations exceeded perceptions, requiring serious efforts to improve the quality of service gap.